2014
DOI: 10.2320/matertrans.m2014053
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ni-Aluminide Surface Layer Containing Hafnium by Molten-Salt Electrodeposition and Cyclic-Oxidation Resistance

Abstract: The preparation of a coating consisting of Ni aluminide containing a small amount of Hf was carried out by the electrodeposition of Ni using an aqueous solution and the electrodeposition of Hf and Al using a molten salt. Furthermore, in order to change the depth of the layer containing Hf in the coating, a four-step electrodeposition of Ni, Hf, Ni and Al was carried out, and the times of the first and third Ni electrodepositions were changed. As a result, coatings consisting of Ni aluminide, which contained di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Furthermore, we showed that the coatings consisting of Ni aluminide (Ni 2 Al 3 ) were formed by the Al electrodeposition on the Ni plate or Ni film using a molten salt at 1023 K. 5,6) Though these coatings had a high oxidation resistance during the isothermal oxidation test, 5) they showed a mass loss due to spallation of a scale during a cyclic-oxidation test. 6) In order to improve a cyclic-oxidation resistance of the coating, we tried electrodeposition of Hf, 6,7) Zr 8) or Y 9) with Al using a molten salt at 1023 K. As a consequence, we succeeded in the preparation of a coating consisting of Ni aluminide containing small amounts of Hf, Zr or Y. Such coatings showed high cyclic-oxidation resistance in air at 1423 K.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we showed that the coatings consisting of Ni aluminide (Ni 2 Al 3 ) were formed by the Al electrodeposition on the Ni plate or Ni film using a molten salt at 1023 K. 5,6) Though these coatings had a high oxidation resistance during the isothermal oxidation test, 5) they showed a mass loss due to spallation of a scale during a cyclic-oxidation test. 6) In order to improve a cyclic-oxidation resistance of the coating, we tried electrodeposition of Hf, 6,7) Zr 8) or Y 9) with Al using a molten salt at 1023 K. As a consequence, we succeeded in the preparation of a coating consisting of Ni aluminide containing small amounts of Hf, Zr or Y. Such coatings showed high cyclic-oxidation resistance in air at 1423 K.…”
Section: Introductionmentioning
confidence: 99%